Produksi Biolistrik dengan Microbial Fuel Cell (MFC) dari Bakteri Termofilik - Vestimarta, Aldi Wahyuda; Irdawati, Irdawati (Lembaga Yasin AlSys, 2024)
The current availability of electrical energy is not proportional to the large demand. This emphasizes the importance of saving electrical energy. To replace fossil fuel power plants that cannot be renewed. So Microbial Fuel Cells (MFC) is used, which is a technology that is able to convert chemical energy from organic matter into electrical energy through the process of oxidation and metabolism of anaerobic bacteria in electroactive biofilms at the anode. This study aims to determine the production of bioelectricity with Microbial Fuel Cell using consortium thermophilic bacteria on TMM substrate. This research was conducted in November 2023 in the microbiology laboratory, FMIPA, UNP. Data analysis was carried out descriptively by displaying images and graphs. Observation of the development of SSA 16 thermophilic bacteria was carried out for 24 hours by checking the voltage once every 2 hours. And the highest voltage result was 749 mv at the 10th hour of measurement.